Loads of training to develop endurance in some physiological variables of the two league and respiratory - Khaleel, Nabil (Journal of Physical Education, 2009)
The Study was conducted on (30) pupils of fifth secondary in Abu- aobeda abn al-jarah school in scholastic year (2008/2009) and in age (17) years. Results showed some significant differences between the pre and post tests to some physiology variables for circulatory and respiratory systems (HEART RATE, PWC170, Vo2MAX and VITAL CAPACITY) From these results this study finds also affect positive for the training load to some physiology variables.